Application of rheology gauge to determine rock competency in Taili, western Liaoning, NE China. (January 2020) - Wan, Le; Zeng, Zuoxun; Acharyya, Sankha Subhra; Swindle, Carl; Li, Huang
Abstract: The intensive deformation along with the rheological behavior of the tectonic units in Taili, eastern North China Craton (NCC), are recognized as the manifestation of the presence of the NE–SW striking ductile shear zone in the region. The presence of two types of granitic veins (aplitic and pegmatitic) in Taili exhibit obvious strain refraction and boudinage structures. Ten samples from different rock types are collected to analyze their deformation characteristics and the rheological properties. The analysis is performed by measuring the rock competency following the methods of mainly two types of rheology gauges: (1) Pinch-and-swell structures, and (2) refraction of the veins. We conclude that two main factors control the deformation patterns in Taili, i.e., grain size and proportion of the mineral component. Grain size is found to be one of the dominant factors, controlling the deformation pattern, i.e., the larger the grain size the higher the rock viscosity is. The proportion of the mineral content is another important parameter which is critical to infer the rheological contrast along with the deformational style of the studied region. The rock viscosity of the samples is inversely proportional to the mica and feldspar content of the same. Micro-structural observation suggests that these rocks experienced strong extensional deformation at a low to middle-temperature condition (around 450–550 °C) during the Mesozoic. This event transformed the granitic veins into boudins associated with intensive strain-refraction which are also responsible for the formation of voluminous felsic rocks with high viscosity contrast in this region. Highlights: We firstly demonstrate the quantitative description of rock competency of the granitic rocks in Taili. The rock particle size is the most dominant factor affecting the rheology as well as the deformation mechanism of rocks. The coarser the mineral particle size, the higher the rock viscosity is. The rock component is envisaged to be the second most dominant factor controlling the deformation scenario of them.